Trypanosoma cruzi Recombinant Complement Regulatory Protein: a Novel Antigen for Use in an Enzyme-Linked Immunosorbent Assay for Diagnosis of Chagas' Disease - Meira, Wendell S. F. (American Society for Microbiology, 2002)
Currently, diagnosis of Chagas' disease is based on serological methods, but due to the high occurrence of inconclusive results, more reliable methods are needed. The use of recombinant antigens for serodiagnosis of Chagas' disease is recommended in order to increase the sensitivity and specificity of the serological tests. The Trypanosoma cruzi complement regulatory protein (CRP) is a surface glycoprotein present on the trypomastigote forms of the parasite, and the recombinant CRP (rCRP) was cloned in a mammalian expression system and purified by affinity chromatography. The purified recombinant protein was used as an antigen in an enzyme-linked immunosorbent assay (rCRP ELISA) in order to verify its sensitivity and specificity compared with other established methods. In this evaluation, a panel of 184 serum samples distributed among chronic chagasic patients (n = 65), blood bank donors (n = 100), and patients infected with Leishmania spp. (n = 19) was used. The sensitivity and specificity of the rCRP ELISA were 100% when compared to conventional serology and complement-mediated lysis tests from these groups. When hemoculture and PCR tests were evaluated for diagnosis of chronic chagasic patients, using the rCRP ELISA as a reference test, the positivities were found to be 64.62 and 81.54%, respectively, showing a higher degree of sensitivity of the test. The data demonstrate that rCRP ELISA was able to discriminate between chronic chagasic patients and nonchagasic individuals, such as blood donors and patients with leishmaniasis. Thus, the rCRP is an excellent antigen for use in Chagas' disease diagnosis, due to the absence of false-negative or false-positive results.